The effectiveness of music therapy treatment to decrease the post-partum blues symptom at private practice midwife (BPM) in the working region of public health center (Puskesmas) IV South Denpasar - Witari, N. N. Deni; G. A., Martha Winingsih (International Journal of Research in Medical Sciences, 2018)
Background: The failure of post-partum mother in adapting to physical and emotional change oftentimes causes psychological disorder such as sadness, exasperation, tiredness, anger, and despair. At Denpasar City, the prevalence of post-partum blues depression based on EPDS score is 20.5%. Music therapy is an alternative to decrease emotional disturbance because music that enters pituitary gland could give response towards emotion through negative feedback on adrenal gland to suppress the release of stress hormones. Methods: The method which used in this research was quasi-experiment design with the framework of one group pre-test-post-test design on post-partum mothers in the seventh day after normal labor and did not experience hearing loss. The pre-test utilized EPDS questionnaire, if there had been a symptom of post-partum blues, they were given Mozart classical music therapy for 7 days and evaluated by questionnaire on the 14th day. Results: From the research on 30 post-partum blues sufferers, prior to the treatment of classical music therapy, it was found that the majority which was 24 respondents (80%) showed mild symptom with the mean value of 7.4. After the treatment of Mozart classical music, almost half of them or 11 respondents (36.7%) did not show post-partum blues symptom with the mean value of 1.4. There is an impact of Mozart classical music therapy treatment toward the decrease of post-partum blues symptom with the P value=0.00. Conclusions: In conclusion, Mozart classical music therapy is effective to decrease the post-partum blues symptom from the scale of 7.4 to 1.4 with p value (0.000).